Prioritizing Zakat Core Principles Criteria - Aam Slamet Rusydiana; Irman Firmansyah (Faculty of Economic and Business, 2017)
Prioriting Zakat Core Principles CriteriaZakat Institution (OPZ) is the intermediary organizations based on social. The entire of operating expense is taken from the zakat and infaq funds collected. The Zakat Core Principles are a starting point for the frameworks and standards of zakat-based governance best practices. The Zakat Core Principles is mainly aimed to improve the quality of the zakat systems by identifying such weaknesses in the existing of supervision and regulation. This study try to prioritize the Principles of ZCP and also the essential criteria from each level using Analytic Hierarchy Process (AHP).There are five core principles of charity principle, consisting of: regulation, supervision, collection and disbursement management, risk management, and audit and transparency. From these principles, the main priority is regulation following with audit and transparency.DOI: 10.15408/ess.v7i2.5275